Symbolic computation system for dynamical application programming - Doroshenko, A.Yu.; Shevchenko, R.S. (Інститут програмних систем НАН України, 2015)
The system of symbolical computation intended for embedding in the industrial applications with the purpose of maintenance to their flexibility and tenability on the varied requirements and a condition of functioning is described. The method of immersion of adjusted program systems in industrial complexes based on use of declarative means of programming at the description of interactions a program component with the environment is offered. The method allows considerably to reduce cost of development of the complex software and also to solve problems of the analysis and maintenance of reliability of a program code.